The intensification of drug therapy for diabetes and its complications: evidence from 2 HMOs - Nau, David P; Garber, Mathew C; Herman, William H (The American journal of managed care, 2004)
To identify trends in the utilization of multidrug therapy for glycemic control, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEIs/ARBs), and lipid-modifying agents for persons with diabetes from 1997 to 2001. The trends in drug and total expenditures for diabetes patients also were examined. Cross-sectional analysis for each year from 1997 through 2001. Subjects were identified from pharmacy and medical claims data by using Health Employer Data and Information Set diabetes indicator criteria, with the additional criterion that subjects must be receiving drug therapy for diabetes. All subjects were continuously enrolled within the commercial segment of 1 of 2 health maintenance organizations (HMOs) in different geographic areas. The proportion of patients in each year who used multiple antihyperglycemic agents was measured, as was the proportion of diabetes patients receiving ACEI/ARBs or lipid-modifying agents. Drug and total expenditures were estimated for the subjects in each HMO. Both HMOs experienced a substantial growth in the proportion of patients receiving multidrug therapy for glycemic control from 1997 to 2001. HMO 1 saw an increase from 27.1% to 43.4%; the increase in HMO 2 was from 27.3% to 39.6%. The use of ACEI/ARBs and lipid-modifying agents nearly doubled during this time period. Expenditures for drugs increased at a much greater rate than medical expenditures. The intensity of drug therapy for persons with diabetes increased between 1997 and 2001. Consequently, drugs now represent a greater proportion of total expenditures for persons with diabetes.